1986
DOI: 10.1088/0031-8949/33/2/001
|View full text |Cite
|
Sign up to set email alerts
|

The Discrete Spectrum States of Finite-Dimensional Quantum Systems Connected with Lie Algebras

Abstract: We consider the problem of finding the energy levels and wave functions of discrete-spectrum states for a class of Hamiltonians connected with root systems of the Lie algebras and in the limit case describing quantum systems of N interacting particles on a straight line in the Morse potential. It is shown that this problem may be reduced to an algebraic problem. Exact expressions are obtained for the dependence of energy levels on parameters of the interaction potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 10 publications
0
21
0
3
Order By: Relevance
“…Bessel polynomials [26], was first given by Inozemtsev and Meshcheryakov [22]. A further study of this case can be found in [19].…”
Section: Construction Methodmentioning
confidence: 94%
“…Bessel polynomials [26], was first given by Inozemtsev and Meshcheryakov [22]. A further study of this case can be found in [19].…”
Section: Construction Methodmentioning
confidence: 94%
“…Показано, что в случае систем СМ фермионов (s = 1/2) применение волновых функций типа Джастроу позволя-ет находить энергию основного состояния и некоторую часть дискретного спектра, характеризуемую "спиновыми" возбуждениями. Должны также существовать воз-буждения "пространственного" типа, подобные найденным для бесспиновых систем СМ бозонов [8]. На этом этапе пока неясно, как модифицировать анзац (20), чтобы можно было рассматривать такие возбуждения.…”
Section: Discussionunclassified
“…Единственным исключением является предел b α → +∞ при масштабировании параметров A α экспонентой e −bα , α = 1, 2, [8], что приводит к однопараметрическо-му потенциалу Морзе…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The only exception is the limit b α → +∞ under the rescaling A α with e −bα , α = 1, 2, [8], which results in the one-parameter Morse potential…”
Section: Introductionmentioning
confidence: 99%